A new protocol for the management of Robin sequence. Issue 5 (September 2015) - Ramanathan, Manikandhan; Pendem, Sneha; Sailer, Hermann F.; Parameshwaran, Ananthnarayanan
Abstract: Aim: The aim of this paper is to put-forth a protocol for the successful management of patients with Robin sequence reducing the morbidity. Subjects and methods: Three patients with Grade 3 PRS reported to us in a failure to thrive scenario. All of them presented within 3–4 weeks of birth with low birth weight. These patients were successfully managed NG tube feeding initially followed by endoscopic airway assessment with simultaneous tongue lip adhesion and mandibular distraction at a later date. Results: All the patients managed by our protocol showed a significant improvement in the airway status minimizing the respiratory efforts, definite weight gain and good quality of life. Conclusion: Judicious timely intervention is essential for management of Robin sequence to achieve successful results. The protocol put forward in this paper helps achieve good results with minimal morbidity.